Confirmation of dicamba-resistant Palmer amaranth in Tennessee - Foster, Delaney C.; Steckel, Lawrence E. (Weed technology, 2022)
Palmer amaranth has a long history of evolving resistance to herbicides to the point at which it has become a significant obstacle to row crop production. A survey of Palmer amaranth escapes in dicamba-resistant cotton and soybean fields in Tennessee was conducted in fall 2021 with the objective of determining whether poor control was due to environmental phenomena or the development of dicamba resistance. A greenhouse dicamba dose-response screen was conducted on 15 Tennessee accessions. Three accessions were identified with a relative resistance factor between 1.85 and 2.49, and one accession from Lauderdale County was found with a relative resistance factor of 14.25. The Lauderdale County 1 accession developed a higher dicamba resistance level than all others evaluated and can no longer be effectively controlled using dicamba. The history of Palmer amaranth escaping dicamba in the Lauderdale County 1 location from 2019 to 2021 in the field and in preliminary greenhouse screens would suggest that the dicamba resistance has passed between generations. This research documents the first findings of Palmer amaranth control failures in cotton and soybean fields due to the evolution of dicamba resistance. Nomenclature: Dicamba; Palmer amaranth, Amaranthus palmeri S. Wats.; cotton, Gossypium hirsutum L.; soybean, Glycine max (L.) Merr.